Impact of major emergencies on zero hunger, achieving food security, and improving nutrition - Fang, Zhong; Xiao, Qiqi; Gao, Yuan (Frontiers in Sustainable Food Systems, 2024)
Food security is a common livelihood issue that has received much attention from countries all over the world. Thus, researching the impact of COVID-19 on eradicating hunger, achieving food security, and improving nutrition can provide experiences for effectively responding to future emergencies that may affect food security. Previous studies on the impact of COVID-19 on food security are less concerned with its impact on improving nutrition, therefore, this paper opens the black box of the process of eliminating hunger, reaching food security and improving nutrition, and divides it into the agricultural production sub-stage and the elimination of hunger and improvement of nutritional sustainability sub-stage. On the other hand, most of the past studies are based on impact pathway analysis only, and lack the assessment of the degree of impact from a quantitative perspective. Therefore, this paper takes the data of 29 provinces in China from 2016 to 2020 as the object of the study to measure their total and sub-stage efficiencies in the process of eradicating hunger, reaching food security, and improving nutrition, and to explore the characteristics of their spatial distributions. Meanwhile, the focus is concentrated on the 2019-2020 window to explore the impact of Covid-19. Based on research findings，this paper puts forward policy recommendations such as establishing a sound natural disaster prevention and control mechanism and accelerating agricultural technological innovation in order to better reduce the negative impact of food security emergencies in the future.